Refugee-Led Organizations' Crisis Response during the COVID-19 Pandemic - Odessa Gonzales Benson; Irene Routte; Ana Paula Pimentel Walker; Mieko Yoshihama; Allison Kelly (Refuge, 2022)
Scholarship on disaster response and recovery has focused on local communities as crucial in developing and implementing timely, effective, and sustainable supports. Drawing from interviews with refugee leaders conducted during the spring and summer of 2020 at the onset of the COVID-19 pandemic, this study examines crisis response activities of refugee-led grassroots groups, specifically within Bhutanese and Congolese refugee communities in a midwestern metropolitan area in the US resettlement context. Empirical findings illustrate how refugee-led groups provided case management, outreach, programming, and advocacy efforts to respond to the pandemic. These findings align with literature about community-based and strengths-based approaches to addressing challenges stemming from the pandemic. They also point to local embeddedness and flexibility as organizational characteristics that may have helped facilitate crisis response, thereby warranting reconsideration and re-envisioning of the role of refugee-led grassroots groups in crisis response.